Vietnam Urbanization Review : Technical Assistance Report - World Bank (World Bank, 2012)
As Vietnam enters a crucial period of urbanization corresponding to its present stage of economic development, the Government of Vietnam has placed strong emphasis on developing its system of cities. In accordance with this objective this Urbanization Review is dedicated to understanding the key dimensions and aspects of Vietnam's urbanization process and to identifying trends, opportunities, challenges and core policy priorities that the government will need to address in order to realize its objective. The Vietnam Urbanization Review was prepared following extensive consultations with various stakeholders, including officials from national and local government, private sector groups and international and bilateral organizations active in development assistance in the urban sector in Vietnam. It builds on a strong portfolio of World Bank engagements in investment and policy lending to the Government of Vietnam. It also builds on a number of more in-depth studies that were commissioned specifically for the Vietnam urbanization review.